The Effect of Dhikr Therapy on the Cardiac Chest Pain of Acute Coronary Syndrome (ACS) Patients - Pangestika, Destiya Dwi; Trisyani, Yanny; Nuraeni, Aan (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Cardiac chest pain is a typical complaint experienced by patients with Acute Coronary Syndrome (ACS) in Emergency Departments (EDs). Pharmacological therapy is one major intervention used to reduce cardiac chest pain due to ACS. However, this therapy does not optimally and completely reduce cardiac chest pain; therefore, additional therapy is greatly required.Purpose: This study aimed to examine the effect of Dhikr therapy as one of the additional therapies for the cardiac chest pain experienced by patients with ACS in EDs.Methods: This quasi-experimental research was conducted using a pretest-posttest control group design. As many as 52 patients with ACS were recruited using a consecutive sampling technique and then equally divided to the intervention and control group. The intervention group received both pharmacological and Dhikr therapy approximately for 17 minutes, while the control group only received the pharmacological therapy based on the hospital’s protocol. The Numeric Pain Rating Scale (NPRS) was used to measure the intensity of cardiac chest pain, and both paired and independent t-tests were utilized to analyze the data.Results: The results showed that there was a significant difference in pain reduction in both groups (p=0.000), although the decrease in the intervention group was higher than that in the control group. Furthermore, the pain reduction was significantly different between groups (p=0.021)Conclusion: Dhikr combined with the pharmacological therapy reduced the intensity of cardiac chest pain in ACS patients better than the use of pharmacological therapy alone. Therefore, this study recommends the combination of pharmacological and Dhikr therapy for patients with ACS.